2022
DOI: 10.1128/msphere.00303-22
|View full text |Cite
|
Sign up to set email alerts
|

Aerosolized Hydrogen Peroxide Decontamination of N95 Respirators, with Fit-Testing and Viral Inactivation, Demonstrates Feasibility for Reuse during the COVID-19 Pandemic

Abstract: The COVID-19 pandemic led to unprecedented pressure on health care and research facilities to provide personal protective equipment. The respiratory nature of the SARS-CoV2 pathogen makes respirator facepieces a critical protective measure to limit inhalation of this virus.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…Once the microorganisms were trapped in the fi lter, approximately 1% of the inoculated bacteria were recovered in the buff er solution, and the exact decontamination capacity of each method was unclear. However, other in-vitro studies have demonstrated that many methods tested in this study have effi cient decontamination capacity against viruses and bacteria, including M. tuberculosis [12,[17][18][19]. However, the microorganism trapping capacity of the N95 respirator is high and may not release the captured microorganisms from the fi bre fi ltration system.…”
Section: Discussionmentioning
confidence: 83%
“…Once the microorganisms were trapped in the fi lter, approximately 1% of the inoculated bacteria were recovered in the buff er solution, and the exact decontamination capacity of each method was unclear. However, other in-vitro studies have demonstrated that many methods tested in this study have effi cient decontamination capacity against viruses and bacteria, including M. tuberculosis [12,[17][18][19]. However, the microorganism trapping capacity of the N95 respirator is high and may not release the captured microorganisms from the fi bre fi ltration system.…”
Section: Discussionmentioning
confidence: 83%